Earthquake hazard in the Middle East: an evaluation for insurance and reinsurance purposes - Degg, Martin Robert (1988)
This study provides an analysis of earthquake hazard in the Middle East for insurance and reinsurance purposes. The analysis incorporates important lessons learned from the 1985 Mexican earthquake. It has the following components: a) An in-depth examination of the Mexican earthquake. This has highlighted the strong influence of superficial geology in controlling exposure to earthquake hazard, and of building type and height in controlling vulnerability to damage; b) An analysis of the escalating earthquake risk in the Middle East. It is concluded that this is attributable to rapid rates of population growth, urbanisation and economic expansion, and to the development of marginal areas that are more exposed to earthquakes; c) A regional analysis of the distribution of earthquake hazard, based on 20th century data and a catalogue of historical earthquake activity that has been compiled during the research programme. It is shown that the areas of greatest hazard tend to coincide with the most densely inhabited parts of the region. The analysis has also provided evidence of temporal fluctuations in seismic activity between contiguous tectonic zones; d) The presentation of a new scheme for earthquake hazard zonation, which is designed to meet the specific requirements of insurers and reinsurers. An evaluation of this scheme, using Israel as a case-study, has proven its worth as a basis for detailed insurance-oriented examinations of earthquake hazard and risk; e) A discussion of earthquake risk control. It is concluded that the data and techniques presented in this study can be used to derive hazard and risk assessments that are more accurate than those currently available to the insurance industry. By using such assessments to control its own vulnerability to earthquake loss, the industry can help to stem the escalation of risk that has recently been witnessed in the Middle East.